2015
DOI: 10.1109/tthz.2015.2443562
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Highly Doped Si Through the Excitation of THz Surface Plasmons

Abstract: We excite surface plasmons (SPs) at the surface of highly doped Si using a prism coupler, and we study the propagation properties of these SPs in order to characterize the terahertz (THz) response of the doped semiconductor. Thanks to the long interaction length of the propagating SP with the substrate material, the method is more sensitive than classical THz time-domain spectroscopy in reflection or in transmission. Moreover, we propose a new technique based on measuring the SP signal, for which the delicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This propagating mode was first predicted by Sommerfeld [38] and was studied at even lower frequencies (microwaves) in the 1950s [39][40][41]. Since then, a number of groups have shown that bound surface waves can propagate over distances up to 10-20 cm on a variety of different metals sheets and wires over a broad range of THz frequencies [42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Plasmonic Measurements At Odds With Predictionsmentioning
confidence: 79%
See 2 more Smart Citations
“…This propagating mode was first predicted by Sommerfeld [38] and was studied at even lower frequencies (microwaves) in the 1950s [39][40][41]. Since then, a number of groups have shown that bound surface waves can propagate over distances up to 10-20 cm on a variety of different metals sheets and wires over a broad range of THz frequencies [42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Plasmonic Measurements At Odds With Predictionsmentioning
confidence: 79%
“…Using an experimental system similar to that used in [50], Nazarov and coworkers recently measured the complex permittivity of heavily doped silicon from ~0.1-1 THz, as shown in Figure 9 [53]. They also found that their results did not match the predictions of the Drude model, not only in the magnitude, but also in the variation with frequency.…”
Section: Measurement Of the Optical Constants Of Metals Via The Excitmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods that typically result in higher excitation efficiency of surface waves rely on careful matching of the wavevectors of an incident wave (normally from the side of an analyte) with that of a surface wave, while also employing some type of a directional coupler arrangement. A classic technique based on this principle employs a higher refractive index (compared to that of an analyte) prism coupler, where the incident angle of the excitation wave is chosen in such a way as to match the propagation constant of the incident wave (projection of the wavevector onto the surface plane) with that of a surface wave [51]. Another classic technique achieves matching of the excitation field and surface wave propagation constants by employing diffraction grating inscribed onto the surface [52].…”
Section: Discussionmentioning
confidence: 99%
“…There were attempts to combine the possibilities of SPP refractometry and TDS spectroscopy for study of the surface of metals and semiconductors in the THz range [30][31][32]. A THz radiation pulse was converted into a pulse of broadband SPPs and, after they traveled a macroscopic distance over the sample, the SPPs were inversely converted into bulk radiation, which was detected, and the resulting photocurrent dependence on time was processed by the standard TDS method.…”
Section: Introductionmentioning
confidence: 99%